Aβ anti-idiotypic antibodies are present in intravenous immunoglobulin and are produced in mice following its administration. (June 2015) - Loeffler, David A.; Klaver, Andrea C.; Coffey, Mary P.
Abstract The effects of intravenous immunoglobulin (IVIG) products were recently examined in patients with Alzheimer's disease (AD). Although encouraging results were obtained in pilot studies, later trials produced negative results. The rationale for these studies was that IVIG contains antibodies to amyloid-beta (Aβ). However, if Aβ anti-idiotypic antibodies (antibodies which bind to anti-Aβ antibodies) are present in IVIG or induced by its administration, these antibodies could potentially reduce its neuroprotective effects in AD. The objective of this study was to determine if IVIG contained such antibodies. Enzyme-linked immunosorbent assays (ELISAs) measured specific binding of IVIG Gamunex to purified human anti-Aβ IgG. The mean concentration of its Aβ anti-idiotypic antibodies in four experiments was 1.85 μg/mL (18.5 μg/g IgG; range = 1.82–1.89 μg/mL [18.2–18.9 μg/g IgG]), and their mean percentage of specific binding was 72.2% (range = 68.3–75.3%). We then performed ELISAs to determine if antibodies to purified human anti-Aβ were produced in C57BL/6 mice injected with the IVIG product Gammagard in an earlier study. After subtracting the expected immune response to normal human immunoglobulins, the median concentrations of these antibodies were 15.6 ng/mL (range = 1.2–108.2 ng/mL) in pre-treatment sera and 2419.4 ng/mL (range = 327.4–8478.4 ng/mL) in post-treatment sera. These results indicate that specific Aβ anti-idiotypic antibodies are detectable in IVIG and may be induced in mice by its administration. The presence of Aβ anti-idiotypic antibodies in IVIG products might decrease neuroprotective effects of their anti-Aβ antibodies in AD.